In Situ Growth Engineering on 2D MXenes for Next‐Generation Rechargeable Batteries - Chuanliang Wei; Baojuan Xi; Peng Wang; Zhengran Wang; Xuguang An; Kangdong Tian; Jinkui Feng; Shenglin Xiong (Advanced Energy & Sustainability Research, 2023)
MXene is an emerging 2D material and shows large potential as a substrate for in situ growth of functional materials due to its merits such as large surface area, abundant nucleation sites, structural diversity, superior dispersion ability, blocking agglomeration of nanomaterials, and rich element/kind compositions. The in situ‐formed MXene‐based composites are largely applied in rechargeable batteries in the past several years by acting as active materials, serving as current collectors, decorating separators, and catalyzing electrochemical process. However, a detailed and systematic summary is still lacked. Herein, a review on in situ growth engineering on 2D MXene for next‐generation rechargeable batteries is presented in detail for the first time. Meanwhile, some outlooks and perspectives are put forward. In situ growth engineering on 2D MXenes can be achieved by calcination method, hydrothermal method, solvothermal method, room‐temperature liquid‐phase reduction method, room‐temperature liquid‐phase oxidation method, electrochemical deposition method, in situ polymerization method, vapor deposition method, mechanical milling method, microwave method, composite method, self‐reduction method, coprecipitation method, immersion method, hydrolysis method, etc. These in situ growth strategies can be extended to materials beyond MXenes, such as graphene, MBene, graphdiyne, etc.